Prevention of alcohol and other drug use and related harm in the digital age: what does the evidence tell us?. Issue 4 (July 2016) - Champion, Katrina E.; Newton, Nicola C.; Teesson, Maree
Abstract : Purpose of review: Alcohol and other drug use are major contributors to the global burden of disease. Prevention is critical and evidence is beginning to support the use of online mediums to prevent alcohol and other drug use and harms among adolescents. This study aims to expand the evidence base by conducting a systematic review of recent universal prevention programs delivered by computers and the Internet. Recent findings: A total of 12 papers reporting outcomes from trials of nine universal online prevention programs were identified. Of the identified interventions, five targeted multiple substances, two focused solely on alcohol, one targeted only cannabis and one primarily addressed smoking. The majority of programs were delivered at school; however one was implemented in a primary care setting. Six programs demonstrated significant, but modest, effects for alcohol and/or other drug use outcomes. Summary: Evidence to support the efficacy of computer and Internet-based prevention programs for alcohol and other drug use and related harms among adolescents is rapidly emerging, demonstrating that online prevention is an area of increasing promise. Further replication work, longer-term trials and attempts to increase the impact are required. Abstract : Supplemental Digital Content is available in the text